2017
DOI: 10.1002/hed.24777
|View full text |Cite
|
Sign up to set email alerts
|

Implication for second primary cancer from visible oral and oropharyngeal premalignant lesions in betel‐nut chewing related oral cancer

Abstract: The predictive value and practicality of visible oral and oropharyngeal premalignant lesions make it a potentially valuable marker in follow-ups of patients with a positive betel-nut chewing habit with oral cancer, especially young patients with heterogeneous leukoplakia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Ten studies found that age at diagnosis of index tumour was associated with SPT, showing a higher probability with increasing age (eight of them) (Adjei Boakye et al, 2019 ; Chow et al, 2019 ; Hosokawa et al, 2018 ; León et al, 2020 ; Li et al, 2020 ; Piersiala et al, 2020 ; Zhang et al, 2019 ). Conversely, Min et al (Min et al, 2019 ), Iwatsubo et al ( 2019 ) and Liu et al ( 2017 ) found an increased risk in the younger patients, and Ho et al (Ho et al, 2022 ) a reduced risk in patients older than 64 years.…”
Section: Resultsmentioning
confidence: 95%
See 4 more Smart Citations
“…Ten studies found that age at diagnosis of index tumour was associated with SPT, showing a higher probability with increasing age (eight of them) (Adjei Boakye et al, 2019 ; Chow et al, 2019 ; Hosokawa et al, 2018 ; León et al, 2020 ; Li et al, 2020 ; Piersiala et al, 2020 ; Zhang et al, 2019 ). Conversely, Min et al (Min et al, 2019 ), Iwatsubo et al ( 2019 ) and Liu et al ( 2017 ) found an increased risk in the younger patients, and Ho et al (Ho et al, 2022 ) a reduced risk in patients older than 64 years.…”
Section: Resultsmentioning
confidence: 95%
“…From a total of 829 articles obtained after deleting duplicates, 703 were excluded based on title and abstract and 126 after reading the full text (Figure 1 ). Finally, 38 articles were included in this systematic review: 36 cohort studies (Adams et al, 2019 ; Adjei Boakye et al, 2019 ; Arie et al, 2021 ; Bertolini et al, 2021 ; Bosshart et al, 2021 ; Bugter et al, 2021 ; Bukovszky et al, 2022 ; Cadoni et al, 2017 ; Chow et al, 2019 ; Feng et al, 2017 ; Guo et al, 2021 ; Harada et al, 2017 ; Ho et al, 2022 ; Hosokawa et al, 2018 ; Inoue et al, 2021 ; Iwatsubo et al, 2019 ; León et al, 2020 ; Leoncini et al, 2018 ; Li et al, 2020 ; Lin et al, 2020 ; Liu et al, 2017 ; Martel et al, 2017 ; Milliet et al, 2021 ; Min et al, 2019 ; Nishimura et al, 2021 ; Overwater et al, 2022 ; Petersen et al, 2022 ; Piersiala et al, 2020 ; Sawaf et al, 2022 ; Stepan et al, 2022 ; Su et al, 2019 ; Su et al, 2020 ; Tseng et al, 2017 ; Wang et al, 2017 ; Wang et al, 2019 ; Zhang et al, 2019 ) and 2 case‐control studies (Ni et al, 2018 ; Watanabe et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations